EFFECT OF INTELLECTUAL CAPITAL ON THE FINANCIAL PERFORNMANCE OF BRAZILIAN COMPANIES LISTED ON B3’s IBRX-50 INDEX FROM 2013 TO 2017 (Contextus - Revista Contemporânea de Economia e Gestão, 2019)
This study aims to analyze the effect of the components of intellectual capital on the financial performance of companies of the B3 IBrX-50 Index, Brazilian stock exchange. The components of the VAIC ™ model (PULIC, 1998) were used: human capital (HCE), structural capital (SCE) and employed capital efficiency (EEC). Performance was measured by the financial indicators ROA, ROE, ROS and Market Value, measured by Tobin’s Q. This is a quantitative, descriptive, documentary research, with secondary data from 2013 to 2017 collected from Economática®. Four econometric models were estimated by multiple regression with panel data to test the hypotheses. Results indicate that all components positively affect ROA and ROE; only CEE affects Market Value; HCE positively affects and SCE negatively affects ROS. The study contributes to the empirical analysis of the components of intellectual capital in the Brazilian context.